Use of antiparasitic and antimicrobial drugs during Covid-19 pandemic (Research, Society and Development, 2022)
It was performed an analysis of the dispensing of antiparasitic and antimicrobial drugs during the Covid-19 pandemic, comparing the profile of use of these drugs in previous periods and during the pandemic and identifying self-medication in the use of these drugs. Data collection was carried out at the family pharmacy in the city of Vitória da Conquista, Bahia. The instruments used to obtain data for the research was the HORUS System. Data on the dispensing of Ivermectin, Azithromycin, Hydroxychloroquine and Chloroquine distributed by the city during the Years of 2018, 2020 and 2021 were collected to compare the profile of drug use before the pandemic and during the Covid-19 pandemic. A total of 12,791 prescriptions for ivermectin, azithromycin, hydroxychloroquine and chloroquine were identified, of which 11,338 (88.6%) came from establishments linked to the SUS. The remainder, 1,453 (11.4%), were from private network establishments. The drugs azithromycin, ivermectin and hydroxychloroquine showed an increase in dispensations in the municipality and this increase correlated with the increase in the number of positive cases for Covid-19 in this city. In this way, evaluating the profile of use of these drugs will make it possible, in the future, to understand the impacts of the pandemic on the health of the population, and will contribute to devising effective strategies to minimize possible long-term effects.